Web-Based of Standard Operational Procedures Design for Lecturers as a Realization of Law and Public Hearing Facilities in Universitas Pembangunan Nasional "Veteran" Jawa Timur - Diana Aqidatun Nisa; Amalia Anjani Arifiyanti; Anajeng Esri Edhi Mahanani (Nusantara Science and Technology Proceedings, 2020)
This study aims to find a communication model and standard operational procedure of digital publication design Policies to support lecturers' performance in administration at UPN "Veteran" Jawa Timur, particularly for the functional position. Thus, the model and design hopefully could ensure legal certainty and public hearing media. The method began with identifying the problems that arise regarding the implementation of policies in the university. The sampling technique involved quantitative and qualitative, which utilized non-random sampling in the form of a questionnaire. Then, the formulation of solutions that answer these problems through the identification of problem-solving efforts was generated. The solution was packaged to provide a communication model and digital publication design of the Policy of Standard Operational Procedure for Lecturers in the UPN "Veteran" Jawa Timur. It was found that there were quite problems, especially that there had not been centralized SOP yet. Consequently, many ambiguities occurred so that the lecturers became confused and felt uncertain about the procedure to proceed with their functional position.